2002
DOI: 10.1016/s0140-6736(02)08355-1
|View full text |Cite
|
Sign up to set email alerts
|

Child prostitution: global health burden, research needs, and interventions

Abstract: Child prostitution is a significant global problem that has yet to receive appropriate medical and public health attention. Worldwide, an estimated 1 million children are forced into prostitution every year and the total number of prostituted children could be as high as 10 million. Inadequate data exist on the health problems faced by prostituted children, who are at high risk of infectious disease, pregnancy, mental illness, substance abuse, and violence. Child prostitution, like other forms of child sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(90 citation statements)
references
References 8 publications
3
78
1
6
Order By: Relevance
“…While reliable estimates regarding the number of adolescents involved in the sex industry are unavailable (Stransky & Finkelhor, 2008), the United States remains one of the top three destination countries for human trafficking (Green, 2008). The plight of DMST victims has not received adequate research attention (Clawson, Dutch, Solomon, & Goldblatt Grace, 2009;Willis & Levy, 2002). Historically, victims of DMST were not differentiated from individuals working as prostitutes; they were subject to legal retribution and social stigmatization (Esselstyn, 1968;Flowers, 1998) and considered willing and blame-worthy participants in a victimless crime.…”
mentioning
confidence: 99%
“…While reliable estimates regarding the number of adolescents involved in the sex industry are unavailable (Stransky & Finkelhor, 2008), the United States remains one of the top three destination countries for human trafficking (Green, 2008). The plight of DMST victims has not received adequate research attention (Clawson, Dutch, Solomon, & Goldblatt Grace, 2009;Willis & Levy, 2002). Historically, victims of DMST were not differentiated from individuals working as prostitutes; they were subject to legal retribution and social stigmatization (Esselstyn, 1968;Flowers, 1998) and considered willing and blame-worthy participants in a victimless crime.…”
mentioning
confidence: 99%
“…De acuerdo con esta categoría, proxenetas y traficantes sacan ventaja de menores, que sufrieron abuso en el hogar y padecen problemas de inseguridad económica o de drogadicción, a través de una ardua labor de reclutamiento y utilizando la seducción, la fuerza, la coerción o el engaño para introducir a jóve-nes inocentes y vulnerables en el negocio de la prostitución (Grace et al 2012: 413;Willis y Levy 2002: 1417. El enamoramiento, las amenazas, la adicción a las drogas, la manipulación y la violencia constituyen los medios y técnicas a través de los cuales los proxenetas someten a los menores (Kennedy et al 2007).…”
Section: Conceptualización De La Prostitución De Menoresunclassified
“…Similarly, 54.7 percent of 64 respondents reported at least one miscarriage and 29.7 percent had more than one miscarriage. In addition to enduring abortions and miscarriages with little, if any, clinical attention, trafficking survivors might not have adequate access to prenatal health care and can suffer from pregnancy-complicating sexually transmitted infections, such as HIV [8,10]. Not surprisingly, a study from the United Kingdom showed that the health professional group most likely to encounter trafficked persons is maternity services professionals [11].…”
Section: Health Implications Of Being Traffickedmentioning
confidence: 99%